Direct and inverted repeats elicit genetic instability by both exploiting and eluding DNA double-strand break repair systems in mycobacteria. - Ewelina A Wojcik; Anna Brzostek; Albino Bacolla; Pawel Mackiewicz; Karen M Vasquez; Malgorzata Korycka-Machala; Adam Jaworski; Jaroslaw Dziadek (PLoS ONE)
Repetitive DNA sequences with the potential to form alternative DNA conformations, such as slipped structures and cruciforms, can induce genetic instability by promoting replication errors and by serving as a substrate for DNA repair proteins, which may lead to DNA double-strand breaks (DSBs). However, the contribution of each of the DSB repair pathways, homologous recombination (HR), non-homologous end-joining (NHEJ) and single-strand annealing (SSA), to this sort of genetic instability is not fully understood. Herein, we assessed the genome-wide distribution of repetitive DNA sequences in the Mycobacterium smegmatis, Mycobacterium tuberculosis and Escherichia coli genomes, and determined the types and frequencies of genetic instability induced by direct and inverted repeats, both in the presence and in the absence of HR, NHEJ, and SSA. All three genomes are strongly enriched in direct repeats and modestly enriched in inverted repeats. When using chromosomally integrated constructs in M. smegmatis, direct repeats induced the perfect deletion of their intervening sequences ~1,000-fold above background. Absence of HR further enhanced these perfect deletions, whereas absence of NHEJ or SSA had no influence, suggesting compromised replication fidelity. In contrast, inverted repeats induced perfect deletions only in the absence of SSA. Both direct and inverted repeats stimulated excision of the constructs from the attB integration sites independently of HR, NHEJ, or SSA. With episomal constructs, direct and inverted repeats triggered DNA instability by activating nucleolytic activity, and absence of the DSB repair pathways (in the order NHEJ>HR>SSA) exacerbated this instability. Thus, direct and inverted repeats may elicit genetic instability in mycobacteria by 1) directly interfering with replication fidelity, 2) stimulating the three main DSB repair pathways, and 3) enticing L5 site-specific recombination.